Сценарні варіанти рішень управління стійким розвитком підприємств галузі рослинництва - Соболевська, Л.І. (Економіко-математичне моделювання соціально-економічних систем, 2016)
The author offers an approach to development and analysis of scenario options of decisions in the field of managing the stable development of crop farming enterprises. The choice of the optimal development strategy for enterprises is being made by means of creation of an expert system based on the knowledge domain model in the form of the Bayesian web of trust.